MR IMAGING OF THE BRAIN IN WILSON’S DISEASE. - CHAWALPARIT, O.; DANPUKDEE, K.; SUTHIPONGCHAI, S.; CHIEWVIT, P.; CHUROJANA, A.; APICHONKIT, W. (The ASEAN Journal of Radiology, 2023)
Four cases of proven Wilson’s disease underwent MRI studies of brain. The characteristic appearance of the putaminal lesion with high and low intensity spots centrally and high intensity "frame" peripherally was shown on T2WI.-TSE in three neurologically symptomatic patients. We also found that the gradient echo imaging showed low signal intensity not more pronouncely than the spin echo imaging. The mid brain, brain stem and cerebellar lesions were also seen in symptomatic patients. Some good correlation of the neurological examinations and MRI findings were found.